In-silico Taxonomic Classification of 373 Genomes Reveals Species Misidentification and New Genospecies within the Genus Pseudomonas - Tran, Phuong N.; Savka, Michael A.; Gan, Han Ming (Frontiers in Microbiology, 2017)
The genus Pseudomonas has one of the largest diversity of species within the Bacteria kingdom. To date, its taxonomy is still being revised and updated. Due to the non-standardized procedure and ambiguous thresholds at species level, largely based on 16S rRNA gene or conventional biochemical assay, species identification of publicly available Pseudomonas genomes remains questionable. In this study, we performed a large-scale analysis of all Pseudomonas genomes with species designation (excluding the well-defined P. aeruginosa) and re-evaluated their taxonomic assignment via in-silico genome-genome hybridization and / or genetic comparison with valid type species. Three-hundred and seventy-three pseudomonad genomes were analysed and subsequently clustered into 145 distinct genospecies. We detected 207 erroneous labels and corrected 43 to the proper species based on Average Nucleotide Identity Multilocus Sequence Typing (MLST) sequence similarity to the type strain. Surprisingly, more than half of the genomes initially designated as P. syringae and P. fluorescens should be classified either to a previously described species or to a new genospecies. Notably, high pairwise average nucleotide identity (>95%) indicating species-level similarity was observed between P. synxantha-P. libanensis, P. psychrotolerans – P. oryzihabitans and P. kilonensis- P. brassicacearum, that were previously differentiated based on conventional biochemical tests and / or genome-genome hybridization techniques.